2019
DOI: 10.1080/14397595.2019.1660028
|View full text |Cite
|
Sign up to set email alerts
|

A large observational cohort study of rheumatoid arthritis, IORRA: Providing context for today’s treatment options

Abstract: Real-world evidence, based on real-world data from routine clinical treatment, is becoming increasingly important for providing high-quality medical care. Large-scale cohort studies can provide useful access to some of this real-world evidence, as shown by the IORRA (Institute of Rheumatology, Rheumatoid Arthritis) cohort in Japan. This large cohort study of patients with rheumatoid arthritis (RA) has been surveying enrolled participants since its inception in 2000. In the last 19 years, it has served as a dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 22 publications
1
40
1
Order By: Relevance
“…IORRA is an RA cohort which was established in 2000 at Tokyo Women's Medical University, Japan. 9 All the RA subjects in the IORRA cohort had high-dose CT in a variety of clinical settings. The ILD status of each subject was classified as UIP, probable UIP, non-specific interstitial pneumonia (NSIP), unclassifiable, others and normal according to the international criteria.…”
Section: Study Cohorts and Subjectsmentioning
confidence: 99%
“…IORRA is an RA cohort which was established in 2000 at Tokyo Women's Medical University, Japan. 9 All the RA subjects in the IORRA cohort had high-dose CT in a variety of clinical settings. The ILD status of each subject was classified as UIP, probable UIP, non-specific interstitial pneumonia (NSIP), unclassifiable, others and normal according to the international criteria.…”
Section: Study Cohorts and Subjectsmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic inflammatory disease that causes joint damage, leading to lifelong disability if not adequately treated [1]. Over the past several decades, the landscape of RA treatment has dramatically changed [2]. A treat-to-target principle has emerged with defined therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…The IORRA cohort was established in October 2000 as a single, institute-based, large, observational cohort of Japanese patients with RA at the Institute of Rheumatology, Tokyo Women’s Medical University. Details regarding the purpose and methodology of this study have been reported previously [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. Over 139 publications have described various characteristics of Japanese patients with RA from this large cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have reported various clinical characteristics of osteoporosis in Japanese patients with RA by way of utilizing data from our Institute of Rheumatology Rheumatoid Arthritis (IORRA) cohort study [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. For patients with RA, the prevention of fractures is important to the maintenance of their quality of life (QoL), thus their osteoporosis requires appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%